Avalia????o dos efeitos do laser em baixa intensidade em adolescentes com cervicalgia - Araujo, Deise Sales de (2014)
This study aimed to verify the effects of therapy with low-level laser in the neck in young patients with neck pain (CV) through cervical range of motion -ADM and electromyographic activity of the trapezius descending. The presence of CV was determined by Cervical Disability Index (NDI). This was a randomized, controlled clinical study and blind youth between 17 and 25, regardless of race, that one who had chronic CV, approved under number 29256/2012 by Research Ethics Committee of Universidade Nove de Julho. Thirty five patients contemplated the inclusion and exclusion criteria were recruited and randomly divided into three groups control, placebo and laser therapy. The laser therapy and placebo groups received 14 sessions of laser therapy and laser-placebo, respectively. All groups were assessed before and after 50 days. For data analysis we applied the ANOVA, Shapiro Wilk and paired t- tests. It was found that there was a statistically significant difference (p< 0.05) in ADM extension, flexion, right and left lateral bending and right and left rotation and electromyographic activity in the left descending trapezius compared to placebo and control. Mean comparison of NDI in laser therapy group was p<0,0001. The low level laser therapy increased ADM and electromyographic activity. Immediately after therapy cervical disability was not found in treated individuals. This protocol is registered at Clinicaltrials.gov: NCT01849913.